Functional Characterization of Argininosuccinate Lyase Gene Variants by Mini-Gene Splicing Assay - Wang, Yanyun; Sun, Yun; Liu, Ming; Zhang, Xiaojuan; Jiang, Tao (Frontiers in Genetics, 2019)
Objective: To perform gene detection and gene mutation analysis in a family of inherited metabolic diseases with elevated CIT by MS/MS test. Methods: The peripheral blood samples were collected from the family members, and genomic DNA was extracted for gene diagnosis using the total exon sequencing method. The novel mutation gene was cloned into pEGFP-C1 vector, and the pathogenicity of the mutation was examined in cultured cells in vitro. Results: The clinical diagnosis of the proband as ASA was clear. Two pathogenic mutations, C.281G>T (p.Arg94Leu) and C.208-15 T>A were detected in the ASL gene, and the two mutations had not been reported. The minigene expression in vitro confirmed that C.208-15 T>A could cause aberrant splicing, resulting in the retention of 13 bp in intron 2 to exon 3. In addition, both C.281G>T and C.208-15 T>A resulted in decreased EGFP expression in the vector pEGFP-C1. Conclusion: Two new pathogenic mutations of ASL gene, C.208-15 T>A and C.281G>T, were found in an ASA family, which enriches the mutational profile of the ASL gene and provides a basis for genetic diagnosis of ASA. In addition to the mutation in the exon region, the base change in the intron may cause aberrant splicing of mRNA and lead to abnormal structure and function of the protein.